2015
DOI: 10.1002/2015gl064466
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic source inversion to estimate volume flux from volcanic explosions

Abstract: We present an acoustic waveform inversion technique for infrasound data to estimate volume fluxes from volcanic eruptions. Previous inversion techniques have been limited by the use of a 1‐D Green's function in a free space or half space, which depends only on the source‐receiver distance and neglects volcanic topography. Our method exploits full 3‐D Green's functions computed by a numerical method that takes into account realistic topographic scattering. We apply this method to vulcanian eruptions at Sakuraji… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
129
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 79 publications
(136 citation statements)
references
References 34 publications
(58 reference statements)
6
129
1
Order By: Relevance
“…However, in a realistic atmosphere, acoustic wave propagation is significantly affected by atmospheric layered structure, wind, and topography (e.g., mountains and buildings). The waveform inversion technique [Ohminato et al, 1998;Kim et al, 2015] can be used to infer the optimal acoustic source time function for the observed overpressure waveforms. Alternatively, it can be directly obtained from mass flow history of equivalent acoustic source (ṁ(w, t)).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in a realistic atmosphere, acoustic wave propagation is significantly affected by atmospheric layered structure, wind, and topography (e.g., mountains and buildings). The waveform inversion technique [Ohminato et al, 1998;Kim et al, 2015] can be used to infer the optimal acoustic source time function for the observed overpressure waveforms. Alternatively, it can be directly obtained from mass flow history of equivalent acoustic source (ṁ(w, t)).…”
Section: Methodsmentioning
confidence: 99%
“…Acoustic wave interaction with atmospheric structure and topography must be considered to compute accurate Green's functions, which is critical to the accuracy of obtained source time function [Kim et al, 2015]. Acoustic wave interaction with atmospheric structure and topography must be considered to compute accurate Green's functions, which is critical to the accuracy of obtained source time function [Kim et al, 2015].…”
Section: Methodsmentioning
confidence: 99%
“…In this and previous studies, the effects of variable atmosphere, vent geometry, and the local topography on the propagation of infrasound are neglected. Numerical techniques such as finite-difference time-domain can be employed due to their ability to handle complicated phenomena in infrasound propagation, thus allowing inclusion of the effects of topography Lacanna et al 2014;Kim et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Infrasound source processes can often be resolved in detail because path effects on infrasound near the vent are often small (Fee & Garces, 2007;Johnson & Lees, 2010) or predictable and straightforward to correct (Kim et al, 2015). Infrasound source processes can often be resolved in detail because path effects on infrasound near the vent are often small (Fee & Garces, 2007;Johnson & Lees, 2010) or predictable and straightforward to correct (Kim et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Its activity included strombolian, vulcanian, and subplinian explosions separated by intervals with weak or absent surface activity (Arellano et al, 2008;Hall et al, 2015). The asymmetry of Tungurahua's crater and summit ( Figure 1) focuses infrasound northwest and complicates recordings (Kim et al, 2012); these effects can be removed with numeric wave propagation modeling (Kim et al, 2015). The asymmetry of Tungurahua's crater and summit ( Figure 1) focuses infrasound northwest and complicates recordings (Kim et al, 2012); these effects can be removed with numeric wave propagation modeling (Kim et al, 2015).…”
Section: Introductionmentioning
confidence: 99%